Radiologic Parameters Can Affect the Preoperative Decision Making of Three-Column Spinal Osteotomies in the Treatment of Severe and Stiff Kyphoscoliosis. Issue 23 (1st December 2017) - Fan, Hengwei; Li, Xueshi; Huang, Zifang; Sui, Wenyuan; Yang, Jingfan; Deng, Yaolong; Wang, Chongwen; Lang, Chuandong; Yang, Junlin
Abstract : Study Design: Retrospective analysis. Objective: To evaluate whether radiologic parameters affect spine surgeon's osteotomy choice in patients with severe and stiff thoracic kyphoscoliosis. Summary of Background Data: Three-column osteotomies were developed to address severe and stiff kyphoscoliosis. Current choice on osteotomies is based on the morphology of kyphosis, global balance, and locations of the main curvature; however, quantitative basis for decision making is still lacking. Methods: Sixty patients with severe and stiff thoracic kyphoscoliosis who underwent three-column osteotomy in the thoracic spine were classified into four groups according to the grade of osteotomy. The radiologic parameters including maximum scoliosis, maximum kyphosis, deformity angular ratio (DAR; maximum Cobb angle divided by number of vertebrae involved), apical vertebral translation, coronal balance, and sagittal balance were measured and compared. Correlation analysis between the radiologic parameters and the osteotomy grades was conducted. Perioperative and long-term complications were reviewed. Results: The overall scoliosis was corrected from a mean preoperative Cobb angle of 129.1° (range, 90–174°) to 56.4° (range, 14–100°), and overall kyphosis was corrected from 124.3° (range, 64–180°) to 54.3° (range, 11–95°). As the osteotomy grades increased, the mean preoperative maximum kyphosis increased from 104.5° to 151.8° and the mean sagittal DAR (S-DAR) increased from 16.4 to 24.9. Statistically significant between-group differences were found for preoperative maximum kyphosis ( P = 0.001), S-DAR ( P = 0.045), and total DAR ( P = 0.033). Significant correlations were observed between the preoperative maximum kyphosis and the osteotomy grade (r = 0.454, P < 0.001). The S-DAR significantly correlated with the osteotomy grade (r = 0.322, P = 0.012). Conclusion: The preoperative maximum kyphosis and the S-DAR may affect the surgeon's decision on the grade of osteotomies. This may enrich the theoretical basis on preoperative planning and help with patient counseling. Level of Evidence: 4